Breeding soundness evaluation of stall-fed bucks using ultrasonography - SINGLA, M; SAINI, A L; KUMAR, AJEET; KASWAN, S; BRAR, P S (The Indian Journal of Animal Sciences, 2017)
Bucks (20 Beetal and 3 cross (75% Beetal and 25% Boer inheritance), sexually mature (mean age and weight 935.09±86.51 days and 55.10±2.27 kg, respectively), were distributed into 3 groups on the basis of testicular fibrotic lesions examined using ultrasonography. Bucks with mild and extensive fibrotic lesions in one or both the testes were enrolled under T1 and T2 groups against T0 i.e. normal (11) homogenous pattern. Increase of fibrosis lead to significant decline in gross motility, sperm motility and live sperm percentage. It can be concluded that ultrasonographic techniques can be adopted as indicator of reproductive performance of breeding bucks for selection under stall- fed conditions.